(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Ensuring regional environmental and economic security is one of the priorities of the state. The problems of sustainable development of regions and their industrial complexes are considered by many scientists, however, insufficient attention is paid to the analysis of the sustainability of industrial enterprises in the Arctic zone (AZ) and their impact on the ecological and economic security of the region. Many of the problems of theoretical and methodological support for improving this security remain underestimated. For industrial enterprises of the Far North as a part of AZ, it is necessary to use a special approach to the development of methodological aspects of ensuring environmental and economic security due to the significant role that entrepreneurial activity has in the socio-economic development of the region and in the environmental situation.The purpose of the research is the formation of a mechanism to ensure the environmental and economic security of the Russian Arctic zone (RAZ), as a region where industrial enterprises operate. The object of the research was the ecological and economic security of the region of the Arctic zone, which exists in the modern conditions of globalization of the economy and the increasing influence of geopolitical factors. The subject of the study was a set of problems of a theoretical, methodical and applied nature, related to the development and implementation of a model for the development of industrial enterprises in the Arctic zone. The factors limiting the development of industrial enterprises of the Far North are formulated. A system of indicators for the sustainable development of industrial enterprises and the environmental and economic security of the region of the Arctic zone of Russia is proposed. The interrelation of indicators of the development of industrial enterprises of the Arctic zone with the conditions of the external economic environment has been revealed, which made it possible to conclude that the structure of industrial production in the regions of the Russian Arctic is distorted. This, in turn, necessitates the formation of maritime clusters and the development of small and medium-sized businesses in the industrial sector. A comparative description of the key areas of state regulation of industrial enterprises in foreign and domestic practice has been carried out. The recommendations of the possible use (adaptation) of international experience in the Russian Arctic are formulated.